UANG POLITIK DALAM PEMILIHAN ANGGOTA DPRD KABUPATEN BUTON TENGAH TAHUN 2019 - Umar, Firman; Agus, Andi Aco; Santun, La Ode (Jurnal Tomalebbi, 2024)
This research aims to determine the motives and control of political money in the election of members of the Central Buton Regency Regional People's Representative Council (DPRD) in 2019. To achieve this goal, researchers used data collection techniques through interviews. The research data that has been collected and obtained is then analyzed qualitatively to determine the motives and supervision of political money in the 2019 election of members of the Central Buton Regency Regional People's Representative Council. The results of the research show that (1) There are several motives for the money used in the 2019 Central Buton Regency DPRD Member Election (2) Supervision of political money in elections or elections for members of the Regional People's Representative Council (DPRD) is carried out by the election organizers, in this case the Commission General Elections (KPU) and the Election Supervisory Body (BAWASLU) by carrying out several supervision and action against election fraud, in this case political money.